The Influence of National Thinking on the Formation of Abstract Vocabulary (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article identifies the role of the human factor in the formation of abstract words, their place in the vocabulary. The role of rational cognition in the formation of abstract words has been identified. In order to define the human factor, the naming of abstract concepts in the language of backward peoples was analyzed. Examples were given of the expression of the raw mental characteristics of the Uzbek people in language.